Effect of Seed Sources on Seed and Seedling Quality in Acacia nilotica - Suresh, K. K.; Jambulingam, R.; Sekar, I. (Indian Forester, 1997)
Studies conducted on the effect of seed source on the seed and seedling quality revealed that high seed quality and germination have resulted in higher shoot and root length, root/shoot ratio and dry matter of seedlings both during 21 and 90 DAS. This augments the opinion that clay and loamy soils are ideal environment for seed collection in Acacia nilotica. Always avoid areas having clacareous soil layer, red soils and from trees in tank beds which are under prolonged water logging.